2001
DOI: 10.1016/s0959-4388(01)00265-3
|View full text |Cite
|
Sign up to set email alerts
|

Computational approaches to motor control

Abstract: New concepts and computational models that integrate behavioral and neurophysiological observations have addressed several of the most fundamental long-standing problems in motor control. These problems include the selection of particular trajectories among the large number of possibilities, the solution of inverse kinematics and dynamics problems, motor adaptation and the learning of sequential behaviors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
57
0
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(59 citation statements)
references
References 78 publications
1
57
0
1
Order By: Relevance
“…One can also draw an interesting parallel of our work with the equilibrium hypothesis in neuromotor control (Flash & Sejnowski, 2001;Latash, 1993). By rearranging equation 2.1 as follows,…”
Section: Neural Control Of Movementmentioning
confidence: 82%
“…One can also draw an interesting parallel of our work with the equilibrium hypothesis in neuromotor control (Flash & Sejnowski, 2001;Latash, 1993). By rearranging equation 2.1 as follows,…”
Section: Neural Control Of Movementmentioning
confidence: 82%
“…The processes by which animals choose simple paths are not well understood (Hooper 2006). It has been proposed (Sabes 2000;Wolpert and Ghahramani 2000;Flash and Sejnowski 2001) that those paths are chosen that balance motor command amplitude and endpoint tracking, leading to smooth and direct paths involving minimal motor commands and endpoint error.…”
Section: Path Planningmentioning
confidence: 99%
“…It has been suggested that the computations underlying the control of reaching differentiate between kinematics and dynamics (Atkeson, 1989;Flash and Sejnowski, 2001;Shadmehr and Wise, 2004). First, the visual difference vector between the hand and the target is translated into a kinematic plan, i.e., a plan of how the joint angles have to change to bring the hand to the target.…”
Section: Experiments 2: Kinematic Versus Dynamic Execution Errorsmentioning
confidence: 99%